(untitled) (Revista de Ciências Agroveterinárias, 2024)
The effect of the inclusion of whey in the diet of growing female and male lambs was evaluated at the SAIS Pachacutec - Peru. Eighty rejected lambs of the Corriedale breed were selected. Each treatment was randomly distributed in four groups n=20 (10 females and 10 males) and each group was distributed in four treatments: T0 (0% whey); T1 (20% whey); T2 (40% whey) and T3 (60% whey) which were added to the base feed (fresh cow’s milk). The nutritional components of the diet were evaluated and the NRC tables were considered to supply the amount of milk according to their development, growth, and body weight. An adaptation period of five days with the feed and 40 days of trial was carried out. Initial weights (kg), final weights and weight gain (kg), and daily weight gain (g) were recorded. The results showed that there were no differences (p>0.05) for initial weights. On the contrary, final weights and daily weight gain showed significant differences (p<0.05) between treatments and genders. T0 and T1 with male gender showed higher means for final weight (6.247 ± 0.03 kg) and (6.244 ± 0.03 kg) respectively, as well as for daily weight gain (77.7 ± 0.67 g) and (77.7 ± 0.6 g) respectively. The results suggested that the diet with 20% whey and 80% fresh cow milk improved growth and development of rejected lambs.